Indocyanine green‐augmented diode laser therapy vs. long‐pulsed Nd:YAG (1064 nm) laser treatment of telangiectatic leg veins: a randomized controlled trial. (13th August 2013) - Klein, A.; Buschmann, M.; Babilas, P.; Landthaler, M.; Bäumler, W.
<x xml:space="preserve">Abstract</x> What's already known about this topic? In a previous proof‐of‐concept trial we showed that indocyanine green (ICG)‐augmented diode laser therapy (ICG+DL) is a new treatment option for telangiectatic leg veins (TLV), but the optimal treatment parameters and the ICG dose required needed further investigation. What does this study add? To the best of our knowledge, this is the first randomized controlled trial comparing ICG+DL therapy with neodymium‐doped yttrium aluminium garnet laser treatment of TLV. The new treatment option was shown to be safe and significantly more effective than the standard treatment.